Upaya Pencegahan Stunting dengan Nugget Daun Kelor Bersama Mahasiswa KKN UNRI di Desa Beringin Taluk - Ahmad Zulfahmi; Erlangga Putra; Annisa Nur Aliyah; Lala Indriani; Putri Tri Ghaziah; Rima Maisarah; Azyzi Syahren Revina; Al Fajri S; Ade Irma Agustina; Shafira Nurjannah; Indra Suharman (BADAN PENERBIT STIEPARI PRESS, 2023)
Stunting is a global health problem that affects the physical growth and development of children. This study aims to evaluate the effectiveness of using Moringa leaf nuggets in preventing stunting in preschool children. The research method involved 20 children aged 4-8 years who received Moringa leaf nuggets as a daily supplement for 6 months. Child growth parameters, including height, weight, and head circumference, were measured at the beginning and end of the study. The results of the analysis showed a significant increase in the physical growth of children in. Moringa leaf nuggets have the potential to be an easily accessible and effective stunting prevention strategy. This research provides initial support for the use of Moringa leaves as a functional food ingredient in efforts to prevent stunting in preschool children. Further studies are needed to understand the mechanisms and long-term effects of using Moringa leaf nuggets in the context of stunting prevention